Professional studies for midwifery practice - Fraser, Diane (Edinburgh : Churchill Livingstone, 2000)
"This book reviews and analyses the most important topics and key professional issues with which midwives today must be familiar - the underpinning theory and concepts on which good clinical practice must be built." "It covers core aspects of the midwife's increasingly responsible role - accountability, the scope of professional practice, ethical issues, clinical risk management, quality in midwifery - and examines issues related to management - autonomy and teamwork, supervisors and managers. The book also reviews underpinning concepts which a midwife has to face in a variety of ways in practice - accessing information, reflective practice, lifelong learning, cultural issues - and finally looks ahead to ways in which midwives may influence the future of their profession. Covering crucial theoretical issues, this book looks briefly at their application into contemporary practice."--Jacket.
Accessing the literature -- Reflection and articulating intuition -- Female gential mutilation: unveiled and deconstructed -- "Cultural conceptions": lesbian parenting and midwifery practice -- Ethical dilemmas in midwifery practice -- Responsibilities and accountability -- The scope of professional practice -- Autonomy and team work -- Clinical risk management -- Supervisors and managers -- Delivering quality in midwifery practice and education -- Lifelong learning -- Influencing the future.
Includes bibliographical references and index.
Keywords: Midwifery; Midwifery; Midwifery